2003
DOI: 10.1124/jpet.103.054106
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Facilitates Colonic Mucosal Repair in Experimental Ulcerative Colitis in Rats

Abstract: Hepatocyte growth factor (HGF) modulates intestinal epithelial cell proliferation and migration, serving as a critical regulator of intestinal wound healing. In this study, we examined the effect of administration of recombinant human HGF on colonic mucosal damage in vivo. Acute colitis was induced in rats by feeding with 5% dextran sulfate sodium (DSS) for 7 days, and colitis was subsequently maintained by feeding with 1% DSS. On the 5th day of DSS administration, osmotic pumps releasing recombinant human HGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 40 publications
2
86
0
Order By: Relevance
“…It is induced by tumor necrosis factor (TNF)-α and IL-1β activation and is characterized by neutrophil mucosal infiltration (4,9). Most rodent models of UC based on DSS administration employ concentrations between 3% and 7% DSS in drinking water (13,(17)(18)(19)(20)(21)(22) In our study, after 8 days of 5% DSS administration in all groups, the colonic mucosa appeared hyperemic, edematous with hemorrhagic erosions and tiny blood coagula. The body weight decreased gradually and the animals exhibited diarrhea and hematochezia.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…It is induced by tumor necrosis factor (TNF)-α and IL-1β activation and is characterized by neutrophil mucosal infiltration (4,9). Most rodent models of UC based on DSS administration employ concentrations between 3% and 7% DSS in drinking water (13,(17)(18)(19)(20)(21)(22) In our study, after 8 days of 5% DSS administration in all groups, the colonic mucosa appeared hyperemic, edematous with hemorrhagic erosions and tiny blood coagula. The body weight decreased gradually and the animals exhibited diarrhea and hematochezia.…”
Section: Discussionmentioning
confidence: 61%
“…DSS induced UC in rats is a well-established model of inflammatory bowel disease, which is clinically and histologically similar to human UC (12,13). It is induced by tumor necrosis factor (TNF)-α and IL-1β activation and is characterized by neutrophil mucosal infiltration (4,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another growth factor, HGF, is secreted from stromal cells during inflammation and activated by HGF activator, which is activated by thrombin in injured tissues. This growth factor promotes proliferation, activation, and differentiation of intestinal endothelial and epithelial cells during angiogenesis and facilitates mucosal repair in experimental colitis (65,151). Additionally, bFGF is a heparin-binding protein involved in intestinal inflammation and it promotes angiogenesis through endothelial cell proliferation, migration, and differentiation, as well as proliferation of mesenchymal cells (67,154).…”
Section: Angiogenic Mediators In Ibd and Experimental Colitismentioning
confidence: 99%
“…HGF activator and HGF activator inhibitor type-1, both HGF-associated molecules involved in the activation of HGF in injured tissues, are associated with colonic mucosal repair (9,10); HGF expression is increased in inflamed colonic mucosal tissues in patients with ulcerative colitis (11). We previously reported that systemic administration of recombinant human HGF ameliorated experimental colitis in rats (12,13). Perturbed homeostasis between luminal antigens (e.g., commensal bacteria) and mucosal immunity serves as a critical determinant in the development of gut inflammation in IBD.…”
Section: Introductionmentioning
confidence: 99%